Students’ perceived social-emotional competence: The role of autonomy-support and links with well-being, social-emotional skills, and behaviors - Collie, Rebecca J.; Martin, Andrew J.; Renshaw, Lauren; Caldecott-Davis, Kate (Learning and instruction, 2024)
The salience of perceived academic competence has been long understood in educational research. Research is now revealing the salience of perceived social-emotional competence (perceived-SEC; i.e., the sense of being capable in one's social-emotional interactions). However, more research is needed to extend understanding of factors associated with perceived-SEC. Guided by the Social and Emotional Competence School Model, we investigated students' perceived-SEC. We examined the extent to which students' perceptions of autonomy-supportive teaching are linked with perceived-SEC and, in turn, students’ well-being (student-reported positive and negative affect), social-emotional skills (parent-reported cognitive reappraisal and self-reflection), and behavioral outcomes (parent-reported prosocial behavior and conduct problems). The sample comprised 501 Australian students (and their parents/carers). Using bifactor exploratory structural equation modelling, five dimensions of perceived-SEC (for assertiveness, tolerance, social regulation, emotion regulation, and emotional awareness) were examined via a global factor and as specific factors. Then, structural equation modelling was used to examine associations among all variables. Perceived autonomy-support was associated with global perceived-SEC. In turn, global perceived-SEC was associated with all outcomes. Three specific perceived-SEC factors also had unique associations with outcomes (beyond the role of the global factor): perceived competence for tolerance (linked with the two behaviors), emotional regulation (linked with negative affect and the two social-emotional skills), and emotional awareness (linked with self-reflection). Findings yield knowledge about perceived-SEC and hold implications for understanding and supporting students’ well-being, social-emotional skills, and behavioral outcomes. •Five types of perceived social-emotional competence (perceived-SEC) were examined.•A global factor and five specific factors of perceived-SEC were identified.•Perceived autonomy-supportive teaching was linked with global perceived-SEC.•The global factor was linked with well-being, social-emotional skills and behaviors.•Specific factors of perceived-SEC were also linked with several outcomes.